Key factors affecting hydrogen trapping at the inclusions in steels: A combined study using microprint technique and theoretical modeling. (15th May 2022) - Qin, W.; Thomas, A.; Cheng, Z.Q.; Gu, D.; Li, T.L.; Zhu, W.L.; Szpunar, J.A.
Abstract: The factors affecting hydrogen trapping at the non-metallic inclusions (NMIs) are identified by a combined experimental and theoretical study. The calculated results based on the proposed models show that the hydrogen trapping capacities at the NMIs decrease in the order of E b TiC > E b TiN > E b Al 2 O 3 > E b FeO > E b MnS . The interfacial sinking of hydrogen leads to the formation of a silver particle-denuded zone around the NMIs. The elastic property of NMIs is more important for hydrogen trapping than the misfit strain. This work unveils the hydrogen trapping-dependent mechanism on the composition, the misfit strain, the elastic properties, the shape and the size of NMIs. Highlights: Theoretical models are built to calculate hydrogen trapping at the inclusions. Hydrogen distribution around the inclusions is experimentally observed. The hydrogen trapping capacities of the inclusions are theoretically calculated. The experimental results are explained using the proposed theoretical models. The key factors that affect hydrogen trapping at inclusions are determined.